The OPAC:Kenneth Dike Library reconversion project (2002)
The focus of this paper is the re-conversion of manual catalogues to machine-readable form at Kenneth Dike Library, University of Ibadan. It examines the relevance of retrospective conversion of Library records in an attempt to improve library services to users. The paper also examines the various attempts at reconverting the large records of the library from 1975 till date as well as enumerating the activites of the re-conversion team at the in-house re-conversion exercise. It also highlights the problems encountered in the course of the project. The efforts and experiences of the exercise will go a long way to facilitate successful retrospective conversion in other libraries in Nigeria